As Pilhas de Pesos de Dom Manuel I: Contributo para a sua caracterização, inventariação e avaliação - Lopes, Luís Seabra (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
In the scope of an important charter reform, Manuel I of Portugal was particularly careful regarding weights, distributing bronze standards to a significant number of counties. The existence of these standards, which are in the form of nested cup weights (or piles) and are dated of 1499, is well known. However, there isn’t an exhaustive inventory of the extant standards and it remains largely unknown which counties actually acquired such standards. We begin by presenting a brief synthesis on the manueline reform of weights. The general characteristics of the manueline standards are identified and the chronology of their production is discussed. Based on literary sources, including the reports of the evaluations carried out in 1857-1860, and direct search in museums, it was possible to identify the existence of 128 manueline piles of weights and, for 73 of them, the counties to which they belonged. It was also possible to gather evaluations for 265 weight pieces from 42 piles. Based on these evaluations, an estimate of the manueline arratel was computed.